The Effects of Syphilis Infection on CD4 Counts and HIV-1 RNA Viral Loads in Blood: A Cohort Study Among MSM with HIV Infection in Sanglah Hospital Bali-Indonesia - Somia, I Ketut Agus; Merati, Ketut Tuti Parwati; Sukmawati, Dewi Dian; Phanuphak, Nittaya; Indira, IGAA Elis; Prasetia, Made Yogi Oktavian; Amijaya, Komang Agus Trisna; Sawitri, AA Sagung (BALI MEDICAL JOURNAL; Vol 5 No 3 (2016), 2016)
Background: Men who have sex with men (MSM), particularly those with HIV infection, are at high risk for contracting syphilis. However, little is known about the effect of syphilis on HIV-1 RNA and CD4 count among HIV infected MSM. Methods: MSM were enrolled into the MSM-VCT study cohort at Sanglah Hospital in Bali between June 22 nd 2011 to February 13 rd 2012. All participants had anti-HIV test and VDRL test at baseline, with TPHA confirmation for reactive VDRL results. Plasma HIV-1 RNA levels and CD4 counts were measured at baseline and month 6 visits. T-test or non-parametric Mann-Whitney test were used to compare changes in CD4 counts and HIV-1 RNA levels between those with and without syphilis. To analyze difference of baseline and 6 month visit in each group, we used paired students t-test. Results: HIV positive MSM with syphilis co-infection had significantly higher mean baseline CD4 count than those without syphilis (P=0.017). No difference was seen for median baseline plasma HIV-1 RNA between HIV positive MSM with and without syphilis (P=0.885). Mean change in CD4 count from baseline to month 6 was similar between HIV positive MSM with syphilis (n=11) and without syphilis (n=20) (P=0.860). Similarly, no significant difference in median HIV-1 RNA change was identified between those with (n=8) and without syphilis (n=11) (P=1.000). Conclusions: HIV positive MSM with syphilis co-infection had higher CD4 cell counts. However, syphilis influences the changes of CD4 cell count and HIV-1 RNA 6 months after HIV diagnosis, but not statistically significance.
Keywords: MSM, HIV, Syphilis; HIV-1 RNA, CD4 count